Facteur 4 en Nord-Pas de Calais : impacts socio-économiques - Anne-Sophie Stevance; Nicolas Houdant; Antoine Bonduelle (Développement Durable et Territoires)
Cutting the greenhouse gas emissions by four by 2050 will have major consequences on local economies, households and policies. This objective is global, however, consequences will have to be faced and dealt with locally. We have studied the consequences of deep reductions of greenhouse gas emissions in the Nord Pas-de-Calais region by 2020-2050, in particular regarding housing renovation and mobility. Modelling the financial consequences of these necessary policies show that constraints become strong and even unbearable for a majority of household. These results call for well-informed and locally-based policies.